COMPARISON OF BUSINESS VALUE WITH A BUSINESS VISIBILITY STUDY APPROACH BETWEEN THE PRODUCTION OF PANDAN MAT AND LOPAK MAT IN LENGKOK LENDANG - Andi Sri Mulyani Indrawati (Scientia Integritas Utama, 2022)
This research is a quantitative descriptive study that aims to find out how the value of business compares with the feasibility approach of business studies of pandan mat production and lopak mats in Tembeng Putek village. The ‘subjects in the study were pandan mat craftsmen and lopak mats, while the objects in this study were financial and non-financial aspects. The results of this study obtained (a) based on non-financial analysis of market and marketing aspects showed that the overall results of respondents’ responses can be concluded that the efforts of pandan mat craftsmen and lopak mats are worth trying with a feasibility value of 4.1 and 4.3 (b) based on analysis of aspects of the business environment showed that the efforts of pandan mat craftsmen and lopak mat craftsmen are worthy to be tried with the overall results of respondents with an average value of 4.6 for pand mats. an and 4.1 for lopak mats. (c) based on the results of financial aspect analysis shows the efforts of pandan mat crafismen are not feasible and lopak mat craftsmen are worthy of business with an average value of respondents 3.4 and 3.9. (d) Financial analyst B/C Ratio shows a comparison with the results of Rp 0.43 for pandan mats and Rp 1.89 for lopak mats, each showing that pandan mats are not feasible and lopak mats are feasible. (e) based on payback analysis the lopak mat is more feasible compared to pandan mats judging from the results of 0.25 years and 0.02 years respectively.